STUDI PERKERSAN JALAN DAN PERBAIKAN TANAH CRACK PADA RUAS JALAN SITIREJO KECAMATAN WAGIR KABUPATEN MALANG (STA 0 + 000 – STA 1 + 000) - Nyuru, Andri Kering; Rahma, Pamela Dinar (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2019)
Soil crack or base soil is the foundation for the pavement of both the pavement on the traffic and the shoulder. Thus the base ground is the last construction to receive the vehicle loads supplied by the pavement. Soil is a substantial component of subgrade that has different characteristics and behaviors, so that each type of soil has certain characteristics. Soil properties affect the resistance of the above layers. Local roads according to jitden bina marga (1997) is a public road that serves local transport with the characteristics of short distance trips, low average speed and the number of access roads are not restricted. The street pets are meant to make the path fulfill the role as in the design. This research is descriptive to know the description of factors - factors that affect road damage. This research is only done for road status in Sitirejo Wagir Subdistrict, Malang Regency. This study only examines the main factors affecting road conditions that are mainly caused by damage to existing roads in the village of Sitirejo. From the results of field research, obtained damage to Sitirejo Road Area Wagir District, Malang Regency, among others, Cracked Alien Crack (Aligator Crack), deformation, surface texture damage. From result of observation result of damage and based on from Public Works Department Directorate General of Highways, Road Pavement Design Manual, No 02 / M / BM / 2013, improvement corresponding to four points that is Achievement of service level, Implementation of life cycle cost minimization, Consideration of practicality of execution , Efficient use of materials.